Analisis Kebutuhan Air Bersih dan Ketersediaan Air di Perumahan Insirifuri Amban Kabupaten Manokwari: Analysis of Clean Water Needs and Water Availability in the Insirifuri Amban Housing Complex, Manokwari Regency - Xanti M. A. Mandosir; Sudarman; Michael Puturuhu (Universitas Papua, 2025)
This study analyzes the need and availability of Clean Water in Insirifuri Amban Housing, Manokwari, with reference to the Planning Criteria Standards of the Directorate General of Human Settlements (Ministry of Public Works, 1996) and the assumption of SNI consumption (60 lt/person/day). The sample includes 110 housing units (90 occupied) with a total of 369 people. The calculation of needs shows a total domestic consumption of 29,251.2 lt/day (292,512 m³/day) or 106,766.88 m³/year. Based on the rainfall analysis, the average annual rainfall is 267.78 mm and the average volume of rainwater captured per roof (catchment area 66 m²) is 176.74 m³/year. If optimized, the potential for rainwater storage for 90 houses reaches 15,906.6 m³/year, a difference of approximately 90,860.28 m³/year, which is still insufficient for the annual housing needs. These results indicate that the potential of rainwater has not yet met the total need for clean water, so the Housing Management must look for other alternatives to meet the need for clean water.